1990
DOI: 10.1099/00221287-136-9-1895
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of anthracyclines: carminomycin 4-O-methyltransferase, the terminal enzymic step in the formation of daunomycin

Abstract: In the presence of S-adenosyl-L-methionine, cell-free extracts of Streptomyces sp. C5, Streptomyces peucetius ATCC 29050, Streptomyces insignis ATCC 31913 and Streptomyces coeruleorubidus ATCC 31276 0-methylated carminomycin and 13-dihydrocarminomycin to daunomycin and 13-dihydrodaunomycin, respectively. With the corresponding aglycones, carminomycinone and 13-dihydrwarminomycinone, as substrates, no methylated products were detected. Other 4-hydroxyanthracyclines such as aklavin and aclacinomycin A, and 4-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
3

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 15 publications
2
27
0
3
Order By: Relevance
“…We previously found that a methyltransferase activity in crude cell extracts of several daunomycin-producing streptomycetes methylated carminomycin and 13-dihydrocarminomycin (Fig. I), but no other glycones or aglycones tested, suggesting that conversion of carminomycin to daunomycin is the terminal reaction in daunomycin biosynthesis (Connors et al, 1990b). Here we report the partial purification and characteristics of an enzyme from Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously found that a methyltransferase activity in crude cell extracts of several daunomycin-producing streptomycetes methylated carminomycin and 13-dihydrocarminomycin (Fig. I), but no other glycones or aglycones tested, suggesting that conversion of carminomycin to daunomycin is the terminal reaction in daunomycin biosynthesis (Connors et al, 1990b). Here we report the partial purification and characteristics of an enzyme from Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%
“…strain C5 and other daunomycin-producing streptomycetes, an enzyme capable of methylating carminomycin to a product that co-migrated with daunomycin (Connors et al, 1990b). In those studies, AdoMet of very high specific activity [46 Ci (mol 14C-AdoMet)-'] was used to detect the activity in crude cell extracts (Connors et al, 1990b).…”
Section: Analysis Of Cmt Activitymentioning
confidence: 99%
See 3 more Smart Citations